2016
DOI: 10.1200/jco.2014.60.1971
|View full text |Cite|
|
Sign up to set email alerts
|

Correlative Analysis of Genetic Alterations and Everolimus Benefit in Hormone Receptor–Positive, Human Epidermal Growth Factor Receptor 2–Negative Advanced Breast Cancer: Results From BOLERO-2

Abstract: Purpose To explore the genetic landscape of tumors from patients enrolled on the BOLERO-2 trial to identify potential correlations between genetic alterations and efficacy of everolimus treatment. The BOLERO-2 trial has previously demonstrated that the addition of everolimus to exemestane prolonged progression-free survival by more than twofold in patients with hormone receptor–positive, human epidermal growth factor receptor 2–negative, advanced breast cancer previously treated with nonsteroidal aromatase inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
171
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(183 citation statements)
references
References 39 publications
11
171
1
Order By: Relevance
“…Exploratory analysis from BOLERO-2 suggests that the efficacy of everolimus is largely independent of the most commonly altered genes or genetic pathways in HR-positive, HER2-negative breast cancer. 53 The positive results from BOLERO-2 contrast with those reported for HORIZON and this may, in part, be a reflection of the different patient populations, in particular, of the proportion of patients with secondary resistance.…”
Section: Mammalian Target Of Rapamycin Inhibitorscontrasting
confidence: 53%
“…Exploratory analysis from BOLERO-2 suggests that the efficacy of everolimus is largely independent of the most commonly altered genes or genetic pathways in HR-positive, HER2-negative breast cancer. 53 The positive results from BOLERO-2 contrast with those reported for HORIZON and this may, in part, be a reflection of the different patient populations, in particular, of the proportion of patients with secondary resistance.…”
Section: Mammalian Target Of Rapamycin Inhibitorscontrasting
confidence: 53%
“…PIK3CA E542K is an activating mutation found on exon 9 of the PIK3CA gene (15). The BOLERO-2 trial which assessed the efficacy of everolimus plus exemestane for Her2-Neu-negative breast cancer showed a greater progression-free survival benefit with everolimus compared with placebo for patients with a PIK3CA exon 9 mutation compared with those with other PIK3CA mutations (16,17). A recent correlative analysis of genetic alterations and everolimus benefit in hormone-positive breast cancer demonstrated more efficacy in individuals with exon-specific mutations in PIK3CA exon 9 compared with exon 20 (17).…”
Section: Discussionmentioning
confidence: 99%
“…The BOLERO-2 trial which assessed the efficacy of everolimus plus exemestane for Her2-Neu-negative breast cancer showed a greater progression-free survival benefit with everolimus compared with placebo for patients with a PIK3CA exon 9 mutation compared with those with other PIK3CA mutations (16,17). A recent correlative analysis of genetic alterations and everolimus benefit in hormone-positive breast cancer demonstrated more efficacy in individuals with exon-specific mutations in PIK3CA exon 9 compared with exon 20 (17). Preclinically, in MCF7 breast cancer cells harboring the PI3KCA E542K mutation, the combination of everolimus with antiestrogen therapy can inhibit proliferation and trigger apoptotic cell death (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This field is particularly challenging, as some available examples clearly show. For example, considering CDK4/6 inhibitors, preclinical data and phase 1 studies suggested that CCND1 amplification or p16 loss was predictive of response, but the phase 2 PALOMA 1 study, which was designed to specifically address these biomarkers, showed equal benefit of palbociclib, regardless of their status in the tumor [95,42] Another example is the biomarker analyses included in the BOLERO 2 trials, failing to show that biomarkers of dysregulated PI3K/Akt/mTOR pathway could predict for the efficacy of everolimus added to exemestane [96]. On the other hand, the intriguing results of the BELLE2 trial showing that PIK3CA mutations in ctDNA predict for the activity of buparlisib suggest that the status of a biomarker should be assessed at the time the disease is treated.…”
Section: Expert Opinionmentioning
confidence: 99%